Digital open repositories: reliability evaluation based on ISO 16363 criteria - Rodrigues do Amaral Benin, Keli; Hamanaka, Raíssa Yuri; Amorim Gonçalez, Paula Regina Ventura Amorim Gonçalez (Advanced Notes in Information Science, 2022)
Open science is constituted of open access, open data, open reproducible search, open science assessment; open science policies; open science tools; open education; open licensing, citizen science, digital preservation, and open innovation. In this research, we intend to approach open access, constituted by open publication in digital repositories (DRs). DRs are the locus of preservation of digital objects, but how do we ensure that a document stored in a DR will be available for long-term access? The reliability of DRs relates to the long-term preservation of their digital records. The ISO 16363:2012 Space data and information transfer systems – Audit and certification of trustworthy digital repositories establish a set of attributes, responsibilities, and requirements that allow the audit and certification of repositories. The objective of the research is to evaluate the institutional repository of the Federal University of Espírito Santo, the Institutional Repository of the Federal Institute of Amazonas, and the Digital Repository of the Federal University of Rio Grande do Sul according to the requirements demanded by ISO 16363:2012. This article is qualitative research with an exploratory and descriptive objective. We sent a survey to the repository collaborators to conduct the self-assessment according to the ISO's reliability criteria. Long-term preservation and authenticity of the information in digital media become necessary for DRs to be effectively trusted.